Trends in suicide death risk in transgender people: results from the Amsterdam Cohort of Gender Dysphoria study (1972–2017). (12th March 2020) - Wiepjes, C. M.; den Heijer, M.; Bremmer, M. A.; Nota, N. M.; de Blok, C. J. M.; Coumou, B. J. G.; Steensma, T. D.
Abstract : Objective: This study explored the overall suicide death rate, the incidence over time, and the stage in transition where suicide deaths were observed in transgender people. Methods: A chart study, including all 8263 referrals to our clinic since 1972. Information on death occurrence, time, and cause of death was obtained from multiple sources. Results: Out of 5107 trans women (median age at first visit 28 years, median follow‐up time 10 years) and 3156 trans men (median age at first visit 20 years, median follow‐up time 5 years), 41 trans women and 8 trans men died by suicide. In trans women, suicide deaths decreased over time, while it did not change in trans men. Of all suicide deaths, 14 people were no longer in treatment, 35 were in treatment in the previous two years. The mean number of suicides in the years 2013–2017 was higher in the trans population compared with the Dutch population. Conclusions: We observed no increase in suicide death risk over time and even a decrease in suicide death risk in trans women. However, the suicide risk in transgender people is higher than in the general population and seems to occur during every stage of transitioning. It is important to have specific attention for suicide risk in the counseling of this population and in providing suicide prevention programs.